A crystalline GaTiS-AEP organic open framework green photoluminescent source and its preparation method

By preparing GaTiS in an oxygen-free state, GaTiS-AEP compounds are stably formed, solving the problems of rarity and weak Ti-S bond stability in the development of green photoluminescent materials in the prior art, and achieving efficient preparation of green photoluminescent sources.

CN118620617BActive Publication Date: 2025-03-04YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411091137.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-03-04
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

In the prior art, the development of green photoluminescent materials has problems of rarity and weak Ti-S bond stability, which makes it difficult to develop green luminescent crystalline GaTiS organic frame materials.

Method used

GaTiS is prepared in an oxygen-free state, and the GaTiS-AEP compound is stably formed by replacing the placeholding of some gallium atoms. It is also prepared by specific preparation methods such as magnetic stirring, vacuum sealing, time-pulse Joule ultrafast heating, etc., to prepare an efficient crystalline GaTiS-AEP organic open skeleton green photoluminescence source.

Benefits of technology

The efficient preparation of green photoluminescence sources was achieved, and the green luminescence efficiency was improved to 6.3%, the luminescence peak was 525 nm, the half-height width was 130 nm, and good luminescence performance was maintained within the range of -110°C to normal temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118620617B_ABST
    Figure CN118620617B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoluminescent sources, and discloses a crystalline GaTiS-AEP organic open skeleton green photoluminescent source and a preparation method thereof, wherein the preparation comprises: weighing gallium source Ga, titanium source Ti and sulfur source S respectively, placing them in a glass cup with AEP solvent for magnetic stirring, and obtaining a yellow-brown viscous slurry; transferring the slurry to a high borosilicate glass tube, and sealing it after vacuuming; then placing it in a time pulse Joule ultrafast heating device for heating reaction; after the reaction is completed and the room temperature is lowered, the precipitate at the bottom of the glass tube is ultrasonically cleaned and filtered alternately with anhydrous ethanol and deionized water, and finally, after vacuum drying, pale yellow particles are obtained, i.e., GaTiS-AEP organic open skeleton green photoluminescent source. The light source compound component of the invention is GaTiS-APE, and the light source is a single crystal particle, and its green luminescent efficiency reaches 6.3%, and the luminescent peak position is 525 nm. Bright green light can be emitted under the irradiation of excitation light at -110°C to room temperature, and the luminescent peak position does not shift when the ambient temperature decreases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoluminescent sources, and in particular to a crystalline GaTiS-AEP organic open skeleton green photoluminescent source and a preparation method thereof. Background Art

[0002] Fluorescent materials emit visible light after being exposed to visible light, ultraviolet light, etc. They are mainly used in anti-counterfeiting, information encryption, fluorescent lamps, special scene signboards, high-end display devices, fluorescent panels, etc. In the past few years, pure color luminescent materials have been widely used due to their unique dimming characteristics, especially green photoluminescent materials, which can provide a unique human visual experience. Usually, the f-layer electrons of lanthanide compounds can release adjustable visible light emission after being excited and transitioning back to the ground state. However, the strategic position of lanthanide metals in my country is gradually increasing. Therefore, seeking alternative green light emitting materials has become a major direction of current scientific research.

[0003] Crystalline metal sulfide organic framework materials have received much attention due to their unique adjustable components, structures, bonding methods and topological structures. In particular, their structural diversity can adjust optoelectronic semiconductor properties, such as photoluminescence and electroluminescence. The preparation of green photoluminescent materials by adjusting the structural components of crystalline metal sulfides is a major research direction at present. The crystalline organic open framework of GaTiS components has a suitable absorption energy band and emission peak. After being illuminated, it can jump from the organic part to the inorganic framework part, emitting extremely strong green light. However, the transfer mechanism of electrons between organic units and GaTiS frameworks is very complicated, resulting in the rarity of organic GaTiS materials that emit green light. In addition, due to the weak stability of Ti-S bonds, the Ti element is almost non-existent in crystalline metal sulfide organic frameworks. It is very necessary to develop crystalline GaTiS organic framework materials that emit green light. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a crystalline GaTiS-AEP organic open skeleton green photoluminescent source and a preparation method thereof. The green photoluminescent light source has a maximum excitation ability in the excitation light wavelength range of 375 nm to 439 nm, and has a very strong low-temperature luminescence ability. The green photoluminescent light source has a very strong application prospect in the field of cold light signboards, and solves the problems mentioned in the above background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a crystalline GaTiS-AEP organic open skeleton green photoluminescent source, wherein the light source compound component is GaTiS-APE, and the light source is a single crystal particle, and its green luminescence efficiency reaches 6.3%, the luminescence peak is 525 nm, the half-maximum width is 130 nm, and it can emit bright green light under the irradiation of excitation light at -110°C to room temperature.

[0006] On the other hand, to achieve the above object, the present invention also provides the following technical solution: a method for preparing a crystalline GaTiS-AEP organic open framework green photoluminescent source, comprising the following steps:

[0007] S1. Weigh gallium source Ga, titanium source Ti and sulfur source S respectively, place them together with AEP solvent in a glass cup and stir magnetically to obtain a yellow-brown viscous slurry;

[0008] S2. Transfer the yellow-brown viscous slurry into a borosilicate glass tube, evacuate it and seal it;

[0009] S3, placing the sealed glass tube in a time pulse Joule ultrafast heating device for heating reaction;

[0010] S4. After the reaction is completed and the temperature drops to room temperature, the precipitate at the bottom of the glass tube is cleaned and filtered alternately with anhydrous ethanol and deionized water for 10 to 20 minutes to obtain solid particles;

[0011] S5. After vacuum drying the solid particles, pale yellow particles are obtained, namely, GaTiS-AEP organic open framework green photoluminescent source.

[0012] Preferably, in step S1, the mass volume ratio of the gallium source Ga, the titanium source Ti, the sulfur source S, and the AEP solvent is 0.2-0.8 g: 0.1-0.6 g: 0.8-2.5 g: 2.5-25 mL.

[0013] Preferably, the AEP solvent is an ultra-dry AEP solvent, and the preparation of the ultra-dry AEP solvent includes: first removing dissolved oxygen from aminoethylpiperazine AEP in an inert atmosphere of argon to obtain oxygen-free AEP; and then removing water molecules therein by microwave radiation to obtain an ultra-dry AEP solvent.

[0014] Preferably, the gallium source Ga is one of metallic gallium Ga, gallium oxide Ga2O3, and gallium nitrate Ga(NO3)3.

[0015] Preferably, the titanium source Ti is titanium dioxide TiO2 or titanium tetrachloride TiCl4.

[0016] Preferably, the sulfur source S is low-valence sulfur, including sublimated sulfur S, sodium sulfide Na2S or potassium sulfide K2S.

[0017] Preferably, in step S2, the sealing after vacuuming is specifically: vacuuming to a degree of 10 -3 ~10 -5 After the pressure reaches 1000 Pa, the seal is sealed by hydrogen-oxygen welding. The welding method is hydrogen-oxygen flame with external flame, the temperature is 1200~1800℃, and the gas flow rate is 300~2000L.h -1 .

[0018] Preferably, in step S3, the conditions for the heating reaction are specifically: heating at 200-650 °C for 15s-10min, a heating rate of 500-1000 °C / min, a pulse frequency of 20-60 times / s, and a cooling rate of 20-40 °C / min.

[0019] Preferably, in step S5, the vacuum drying conditions are as follows: drying in a vacuum oven at 60-80°C for 5-12 hours, with a vacuum degree of 0.01-0.1×10 -1 Pa.

[0020] The beneficial effects of the present invention are as follows: the present invention adopts the preparation of GaTiS in an oxygen-free state, evacuates oxygen and prepares in a high vacuum, in the compound, titanium atoms can replace the position of some Ga atoms, thereby stably forming a GaTiS-AEP compound, and the introduction of Ti atoms in GaTiS-AEP can improve the luminous efficiency of GaS-AEP from 1.3% to 6.3%. The luminescence peak position is 525 nm, the half-height width is 130 nm, and bright green light can be emitted under the irradiation of excitation light at -110°C to room temperature, and the luminescence peak position does not shift when the ambient temperature decreases. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the XRD graph of the crystalline GaTiS-AEP organic open framework green photoluminescent source prepared in Examples 1 and 2 of the present invention, wherein the illustration in the upper left corner is an optical photograph of the sample prepared in Example 1, the lower curve represents Example 1, and the upper curve represents Example 2;

[0022] Figure 2 The atomic arrangement diagram and unit cell parameters of the sample prepared in Example 1 of the present invention, the photo in the upper right corner is a luminescence photo of the sample under 365nm wavelength excitation;

[0023] Figure 3 The temperature-dependent emission spectrum of the sample prepared in Example 1 of the present invention is

[0024] Figure 4 is the excitation spectrum of the sample prepared in Example 1 of the present invention;

[0025] Figure 5 is a scanning electron microscope image of the sample prepared in Example 1 of the present invention;

[0026] Figure 6 It is the X-ray scattering energy spectrum of the sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] See also Figure 1-Figure 6 The present invention provides a technical solution: a crystalline GaTiS-AEP organic open skeleton green photoluminescent source, wherein the light source compound component is GaTiS-APE, and the light source is a single crystal particle, and its green luminescence efficiency reaches 6.3%, the luminescence peak is 525 nm, the half-height width is 130 nm, and it can emit bright green light under the irradiation of excitation light at -110℃~25℃.

[0029] A method for preparing a crystalline GaTiS-AEP organic open-framework green photoluminescent source. During the preparation process, all raw materials involved are of analytical grade or above.

[0030] The preparation method comprises the following steps:

[0031] S1. Weigh gallium source Ga, titanium source Ti and sulfur source S respectively, place them together with AEP solvent in a glass cup and stir magnetically to obtain a yellow-brown viscous slurry. The mass volume ratio of the gallium source Ga, titanium source Ti, sulfur source S and AEP solvent is 0.2-0.8 g: 0.1-0.6 g: 0.8-2.5 g: 2.5-25 mL.

[0032] AEP solvent is an ultra-dry AEP solvent. The preparation of ultra-dry AEP solvent includes: firstly removing dissolved oxygen from aminoethylpiperazine AEP in an inert atmosphere of argon gas to obtain oxygen-free AEP; then removing water molecules therein by microwave radiation to obtain ultra-dry AEP solvent. The use of ultra-dry AEP solvent is used to prevent dissolved oxygen and water molecules from oxidizing S into high-valent sulfur (sulfate or sulfite) during the reaction process.

[0033] Furthermore, the gallium source Ga is one of metallic gallium Ga, gallium oxide Ga2O3, and gallium nitrate Ga(NO3)3.

[0034] Further, the titanium source Ti is titanium dioxide TiO2 or titanium tetrachloride TiCl4.

[0035] Furthermore, the sulfur source S is low-valent sulfur, including sublimed sulfur S, sodium sulfide Na2S or potassium sulfide K2S. Compounds containing high-valent sulfur (such as sulfate, sulfite) cannot be used.

[0036] S2. Transfer the yellow-brown viscous slurry into a borosilicate glass tube, evacuate it and seal it; evacuate the tube to a vacuum degree of 10 -3 ~10 -5 After the pressure reaches 1000 Pa, the seal is sealed by hydrogen-oxygen welding. The welding method is hydrogen-oxygen flame with external flame, the temperature is 1200~1800℃, and the gas flow rate is 300~2000L.h -1 .

[0037] S3. The sealed glass tube is placed in a time pulse Joule ultrafast heating device for heating reaction; heating at 200-650 °C for 15s-10min, a heating rate of 500-1000 °C / min, a pulse frequency of 20-60 times / s, and a cooling rate of 20-40 °C / min.

[0038] S4. After the reaction is completed and the temperature drops to room temperature, the precipitate at the bottom of the glass tube is cleaned and filtered alternately with anhydrous ethanol and deionized water for 10 to 20 minutes to obtain solid particles;

[0039] The solid particles are vacuum dried (vacuum oven at 60-80°C for 5-12 hours, vacuum degree 0.01-0.1×10 -1 Pa) to obtain light yellow single crystal particles, namely GaTiS-AEP organic open skeleton green photoluminescent source. This luminescent source emits bright monochromatic green light under the irradiation of excitation light. And it can emit bright green light under the irradiation of excitation light at -110℃ to room temperature, and the luminescent peak position does not shift when the ambient temperature decreases.

[0040] Example 1

[0041] The preparation method of the crystalline GaTiS-AEP organic open framework green photoluminescent source comprises the following steps:

[0042] Step 1: Use a pipette to take 2.5-25 mL of aminoethylpiperazine (AEP) in a vacuum glove box filled with argon AR, and leave it open for 1-5 hours until the oxygen content probe in the glove box drops to less than 1 ppm, thereby obtaining oxygen-free AEP.

[0043] Step 2: Add 5-15g of 3A molecular sieve desiccant to the oxygen-free AEP obtained in step 1 and place it in a microwave radiation furnace at a power of 60-300W for 10-25 minutes to remove water molecules in the AEP and obtain an ultra-dry AEP solvent.

[0044] Step 3: Weigh 100-600 mg of metallic gallium (Ga source), 100-600 mg of titanium dioxide (Ti source) and 0.8-2.5 g of sublimated sulfur (S source) on an analytical balance, place them together with ultra-dry AEP solvent in a 100 mL glass cup and stir them magnetically for 0.5-3 hours to obtain a yellow-brown viscous slurry.

[0045] Step 4: Use a pipette and a scraper to transfer the slurry obtained in step 3 into a borosilicate glass tube with a wall thickness of 1 to 2 mm, a diameter of 0.3 to 2 cm, and a length of 3 cm to 30 cm, and use a vacuum tube sealing machine equipped with a molecular turbo pump group to evacuate the tube to a vacuum degree of 10 -3 ~10 -5 Pa, and then sealed with a plug made of the same material.

[0046] Step 5: Take out the vacuumed glass tube from the glove box in step 4 and seal it by welding with an oxyhydrogen machine. The welding method is an oxyhydrogen flame with an external flame, a temperature of 1200-1800°C, and a gas flow rate of 300-2000 L / h. -1 .

[0047] Step six, placing the glass tube welded and sealed in step five in a time pulse Joule ultrafast heating device for heating reaction, heating at 200-650°C for 15s-10min, a heating rate of 500-1000°C / min, a pulse frequency of 20-60 times / s, and a cooling rate of 20-40°C / min.

[0048] Step 7: After step 6 is completed and the temperature drops to room temperature, remove the floccules and excess AEP solvent on the top with a pipette, and use anhydrous ethanol and deionized water to alternately sonicate the precipitate at the bottom (ultrasonic power 20-200 watts, frequency 50 Hz) for 10-20 minutes to remove side reaction impurities and unreacted raw materials attached to the crystal surface.

[0049] Step 8: Transfer the solid particles from step 7 to filter paper and dry them in a vacuum oven at 60-80°C for 5-12 hours with a vacuum degree of 0.01-0.1×10 -1 The light yellow particles obtained by Pa are GaTiS-AEP organic open framework green photoluminescence sources, such as Figure 1 The middle and lower curves show the XRD pattern of the crystalline GaTiS-AEP organic open framework green photoluminescence source. The diffraction peak of the sample is sharp, the peak position is fixed, and there is no impurity peak. It can be seen from the figure that the prepared sample is a pure crystalline structure. Figure 1The illustration in the upper left corner is an optical photograph of the sample. The sample is spread flat on acid-free paper and arranged in an "S" shape. The sample is composed of khaki-colored particles with loose particles.

[0050] The atomic arrangement diagram and unit cell parameters of the sample prepared in this embodiment are as follows Figure 2 As shown in the figure, it can be seen that its basic framework is composed of Ga, Ti, and S elements, and the unit cell parameters are a=18, b=20, and c=21. Ti occupies some Ga sites in GaS-AEP, resulting in slightly different unit cell parameters. Figure 2 The photo in the upper right corner is a luminescence photo of the sample under excitation at a wavelength of 365nm. The "S" pattern formed by the powder emits a bright green light, indicating that the sample has good photoinduced green luminescence ability.

[0051] The variable temperature luminescence spectrum and excitation spectrum of the samples prepared in this embodiment are shown as follows: Figure 3 and Figure 4 As shown by Figure 3 and Figure 4 It can be seen that the luminescence peak temperature of the sample ranges from 163K to 293K (-110-20℃), and as the temperature decreases, the luminescence peak intensity becomes stronger. Figure 4 It can be seen from the excitation spectrum that the sample can reach the maximum luminescence peak intensity when excited by a light source between 375-439nm, indicating that the sample has a wider excitation wavelength range. The fitting of the thick line also shows that the most suitable excitation peak position of the sample is at 396nm.

[0052] The scanning electron microscope and X-ray scattering spectrum of the samples prepared in this example are as follows Figure 5 and Figure 6 As shown by Figure 5 and Figure 6 It can be seen that the sample is a single particle, and its main framework components are Ga, Ti, and S.

[0053] Example 2

[0054] The preparation method of the crystalline GaTiS-AEP organic open framework green photoluminescent source comprises the following steps:

[0055] Step 1: Use a pipette to take 2.5-25 mL of aminoethylpiperazine (AEP) in a vacuum glove box filled with argon AR, and leave it open for 1-5 hours until the oxygen content probe in the glove box drops to less than 1 ppm, thereby obtaining oxygen-free AEP.

[0056] Step 2: Add 5-15g of 3A molecular sieve desiccant to the oxygen-free AEP obtained in step 1 and place it in a microwave radiation furnace at a power of 60-300W for 10-25 minutes to remove water molecules in the AEP and obtain an ultra-dry AEP solvent.

[0057] Step 3: Weigh 200-800 mg of gallium oxide (Ga source), 100-500 mg of titanium dioxide (Ti source) and 0.8-2.5 g of sublimated sulfur (S source) on an analytical balance, place them together with ultra-dry AEP solvent in a 100 mL glass cup and stir them magnetically for 0.5-3 hours to obtain a yellow-brown viscous slurry.

[0058] Step 4: Use a pipette and a scraper to transfer the slurry obtained in step 3 into a borosilicate glass tube with a wall thickness of 1 to 2 mm, a diameter of 0.3 to 2 cm, and a length of 3 cm to 30 cm, and use a vacuum tube sealing machine equipped with a molecular turbo pump group to evacuate the tube to a vacuum degree of 10 -3 ~10 -5 Pa, and then sealed with a plug made of the same material.

[0059] Step 5: Take out the vacuumed glass tube from the glove box in step 4 and seal it by welding with an oxyhydrogen machine. The welding method is an oxyhydrogen flame with an external flame, a temperature of 1200-1800°C, and a gas flow rate of 300-2000 L / h. -1 .

[0060] Step six, placing the glass tube welded and sealed in step five in a time pulse Joule ultrafast heating device for heating reaction, heating at 200-650 °C for 15s-10min, a heating rate of 500-1000 °C / min, a pulse frequency of 20-60 times / s, and a cooling rate of 20-40 °C / min.

[0061] Step 7: After step 6 is completed and the temperature drops to room temperature, remove the floccules and excess AEP solvent on the top with a pipette, and use anhydrous ethanol and deionized water to alternately sonicate the precipitate at the bottom (ultrasonic power 20-200 watts, frequency 50 Hz) for 10-20 minutes to remove side reaction impurities and unreacted raw materials attached to the crystal surface.

[0062] Step 8: Transfer the solid particles from step 7 to filter paper and dry them in a vacuum oven at 60-80°C for 5-12 hours with a vacuum degree of 0.01-0.1×10 -1 The light yellow particles obtained by Pa are GaTiS-AEP organic open framework green photoluminescence sources. Figure 1 The upper middle curve shows the XRD pattern of the crystalline GaTiS-AEP organic open framework green photoluminescence source, from which we can see the crystalline nature of the sample.

[0063] Example 3

[0064] The preparation method of the crystalline GaTiS-AEP organic open framework green photoluminescent source comprises the following steps:

[0065] Step 1: Use a pipette to take 2.5-25 mL of aminoethylpiperazine (AEP) in a vacuum glove box filled with argon AR, and leave it open for 1-5 hours until the oxygen content probe in the glove box drops to less than 1 ppm, thereby obtaining oxygen-free AEP.

[0066] Step 2: Add 5-15g of 3A molecular sieve desiccant to the oxygen-free AEP obtained in step 1 and place it in a microwave radiation furnace at a power of 60-300W for 10-25 minutes to remove water molecules in the AEP and obtain an ultra-dry AEP solvent.

[0067] Step 3: Weigh 100-600 mg of gallium oxide (Ga source), 100-600 mg of titanium tetrachloride (Ti source) and 0.8-2.5 g of sublimated sulfur (S source) on an analytical balance, place them together with ultra-dry AEP solvent in a 100 mL glass cup and stir them magnetically for 0.5-3 hours to obtain a yellow-brown viscous slurry.

[0068] Step 4: Use a pipette and a scraper to transfer the slurry obtained in step 3 into a borosilicate glass tube with a wall thickness of 1 to 2 mm, a diameter of 0.3 to 2 cm, and a length of 3 cm to 30 cm, and use a vacuum tube sealing machine equipped with a molecular turbo pump group to evacuate the tube to a vacuum degree of 10 -3 ~10 -5 Pa, and then sealed with a plug made of the same material.

[0069] Step 5: Take out the vacuumed glass tube from the glove box in step 4 and seal it by welding with an oxyhydrogen machine. The welding method is an oxyhydrogen flame with an external flame, a temperature of 1200-1800°C, and a gas flow rate of 300-2000 L / h. -1 .

[0070] Step six, placing the glass tube welded and sealed in step five in a time pulse Joule ultrafast heating device for heating reaction, heating at 200-650 °C for 15s-10min, a heating rate of 500-1000 °C / min, a pulse frequency of 20-60 times / s, and a cooling rate of 20-40 °C / min.

[0071] Step 7: After step 6 is completed and the temperature drops to room temperature, remove the floccules and excess AEP solvent on the top with a pipette, and use anhydrous ethanol and deionized water to alternately sonicate the precipitate at the bottom (ultrasonic power 20-200 watts, frequency 50 Hz) for 10-20 minutes to remove side reaction impurities and unreacted raw materials attached to the crystal surface.

[0072] Step 8: Transfer the solid particles from step 7 to filter paper and dry them in a vacuum oven at 60-80°C for 5-12 hours with a vacuum degree of 0.01-0.1×10 -1 The light yellow particles obtained by Pa are GaTiS-AEP organic open framework green photoluminescence sources.

[0073] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A crystalline GaTiS-AEP organic open framework green photoluminescent source, characterized in that: The light source compound component is GaTiS-AEP, which is a single crystal particle with a green luminescence efficiency of 6.3%, a luminescence peak of 525 nm, a half-width of 130 nm, and can emit bright green light under the irradiation of excitation light at -110°C to room temperature.

2. A method for preparing the crystalline GaTiS-AEP organic open framework green photoluminescent source according to claim 1, characterized in that: The steps include: S1. Weigh gallium source Ga, titanium source Ti and sulfur source S respectively, place them together with AEP solvent in a glass cup and stir them magnetically to obtain a yellow-brown viscous slurry; the AEP solvent is an ultra-dry AEP solvent; the sulfur source S is sublimated sulfur S, sodium sulfide Na2S or potassium sulfide K2S; S2. Transfer the yellow-brown viscous slurry into a borosilicate glass tube, evacuate it and seal it; S3, placing the sealed glass tube in a time pulse Joule ultrafast heating device for heating reaction; S4. After the reaction is completed and the temperature drops to room temperature, the precipitate at the bottom of the glass tube is cleaned and filtered alternately with anhydrous ethanol and deionized water for 10 to 20 minutes to obtain solid particles; S5. After vacuum drying the solid particles, pale yellow particles are obtained, namely, GaTiS-AEP organic open framework green photoluminescent source.

3. The method for preparing the crystalline GaTiS-AEP organic open framework green photoluminescent source according to claim 2, characterized in that: In step S1, the mass volume ratio of the gallium source Ga, the titanium source Ti, the sulfur source S, and the AEP solvent is 0.2-0.8 g: 0.1-0.6 g: 0.8-2.5 g: 2.5-25 mL.

4. The method for preparing the crystalline GaTiS-AEP organic open framework green photoluminescent source according to claim 2, characterized in that: The preparation of the ultra-dry AEP solvent comprises: firstly removing dissolved oxygen from aminoethylpiperazine AEP in an inert atmosphere of argon gas to obtain oxygen-free AEP; and then removing water molecules therein by microwave radiation to obtain the ultra-dry AEP solvent.

5. The method for preparing the crystalline GaTiS-AEP organic open framework green photoluminescent source according to claim 2, characterized in that: The gallium source Ga is one of metal gallium Ga, gallium oxide Ga2O3, and gallium nitrate Ga(NO3)3.

6. The method for preparing the crystalline GaTiS-AEP organic open framework green photoluminescent source according to claim 2, characterized in that: The titanium source Ti is titanium dioxide TiO2 or titanium tetrachloride TiCl4.

7. The method for preparing the crystalline GaTiS-AEP organic open framework green photoluminescent source according to claim 2, characterized in that: In step S2, the vacuuming and sealing is specifically: vacuuming to a degree of 10 -3 ~10 -5 After the pressure reaches 1000 Pa, the seal is sealed by hydrogen-oxygen welding. The welding method is hydrogen-oxygen flame with external flame, the temperature is 1200~1800℃, and the gas flow rate is 300~2000L.h -1 .

8. The method for preparing the crystalline GaTiS-AEP organic open framework green photoluminescent source according to claim 2, characterized in that: In step S3, the conditions for the heating reaction are specifically: heating at 200-650 °C for 15 s-10 min, a heating rate of 500-1000 °C / min, a pulse frequency of 20-60 times / s, and a cooling rate of 20-40 °C / min.

9. The method for preparing the crystalline GaTiS-AEP organic open framework green photoluminescent source according to claim 2, characterized in that: In step S5, the vacuum drying conditions are as follows: drying in a vacuum oven at 60-80°C for 5-12 hours, with a vacuum degree of 0.01-0.1×10 -1 Pa.

Citation Information

Patent Citations

  • Ti (titanium)-doped gallium oxide crystal, as well as preparation method and application thereof

    CN107201543A